a The Influence of Individual Characteristics on Job Satisfaction in Health Center Employees - Hanifah Hanifah; Erini Junita Sari; Ika Sri Lidya Putri; Zainal Arifin (UrbanGreen, 2022)
This study aims to determine the effect of individual characteristics on job satisfaction at Teluk Tiram Public Health Center employees. Individual characteristics in this study focused on interests, attitudes, abilities and moods. Meanwhile, job satisfaction focuses on salaries, promotions, supervision (relationships with superiors), co-workers and the work itself.This research is a quantitative research with causality design. The population in this study were all employees of the Teluk Tiram Community Health Center totaling 36 respondents, with a questionnaire as a research instrument. The research hypothesis was tested using simple linear regression analysis using the SPSS version 25 program.The results showed that individual characteristics had a significant effect on job satisfaction at Teluk Tiram Health Center employees, indicated by a significant value of 0.000 <0.05 and a t-count value of 6.371. Therefore, individual characteristics variables have a significant and significant effect on job satisfaction for employees of Teluk Tiram Public Health Centers.